2016
DOI: 10.1016/j.jphs.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of extracellular matrix production and remodeling by doxycycline in smooth muscle cells

Abstract: Alterations in the extracellular matrix (ECM) production and remodeling of smooth muscle cells (SMCs) have been implicated in processes related to the differentiation in atherosclerosis. Due to the anti-atherosclerotic properties of the tetracyclines, we aimed to investigate whether cholesterol supplementation changes the effect of doxycycline over the ECM proteins synthesis and whether isoprenylated proteins and Rho A protein activation are affected. SMC primary culture isolated from chicks exposed to atherog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Unlike doxycycline, which has been shown to improve cardiac remodeling in several studies [ 5 , 9 , 19 , 20 ], there are very few studies regarding the use of minocycline for the inhibition of MMP activation and, thereby, cardiac remodeling. One experimental study showed that minocycline could protect the adult rat cardiac myocytes against simulated ischemia-reperfusion injury by inhibiting poly (ADP-ribose) polymerase-1 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike doxycycline, which has been shown to improve cardiac remodeling in several studies [ 5 , 9 , 19 , 20 ], there are very few studies regarding the use of minocycline for the inhibition of MMP activation and, thereby, cardiac remodeling. One experimental study showed that minocycline could protect the adult rat cardiac myocytes against simulated ischemia-reperfusion injury by inhibiting poly (ADP-ribose) polymerase-1 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that in some cases, calcification maybe also related to vascular remodeling, which could ECM remodeling and even restenosis. , We evaluated three genes (MMP-2, COL3A1, and COL17A1) that are involved with ECM remodeling. MMP-2 is one member of the matrix metalloproteinase family strongly related to ECM degradation, leading to plaque instability and rupture. Figure D shows that PA-YKNO coating could significantly reduce MMP-2 expression. Additionally, COL3A1 and COL17A1 are associated with ECM remodeling leading to restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…More tentatively, it is also possible that the effects of MMP on memory are not (only) conferred via LTP but via other mechanisms, including the configuration of extracellular matrix. Indeed, doxycycline affects extracellular matrix structure (Palomino-Morales et al, 2016), and different structural components of the matrix are suggested to impact on memory (Gogolla et al, 2009; Tsien, 2013; Happel et al, 2014; Banerjee et al, 2017). The turnaround time of the extracellular matrix is much longer than that of individual proteins (Tsien, 2013), thus explaining a long-lasting impact of doxycycline treatment.…”
Section: Discussionmentioning
confidence: 99%